Implementation of 21st Century Learning at PAUDQU Daarul Fath Pengging in 2024 - Mujahidatin, Sri; Seno, Seno; Rondli, Wawan Shokib; Darmuki, Agus (Universitas Muhammadiyah Ponorogo, 2024)
This research aims to analyze the application of 21st-century learning at PAUDQU Daarul Fath Pengging, Boyolali Regency. A qualitative descriptive approach was used, with the principal and three teachers from PAUDQU Daarul Fath serving as the subjects. Data was collected through observation, interviews, and documentation. The analysis was conducted using the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing/verification.The results of this research indicate that PAUDQU Daarul Fath Pengging has effectively implemented 21st-century learning strategies. The learning approach integrates modern educational techniques with traditional Islamic boarding school methods, providing a comprehensive and balanced education to the students. This implementation reflects a commitment to preparing students with the necessary skills for the future while maintaining their cultural and religious foundations.